2021
DOI: 10.1093/ndt/gfab223
|View full text |Cite|
|
Sign up to set email alerts
|

Chronic kidney disease and neurological disorders: are uraemic toxins the missing piece of the puzzle?

Abstract: Chronic kidney disease (CKD) perturbs the crosstalk with others organs, with the interaction between the kidneys and the heart having been studied most intensively. However, a growing body of data indicates that there is an association between kidney dysfunction and disorders of the central nervous system. In epidemiological studies, CKD is associated with a high prevalence of neurological complications, such as cerebrovascular disorders, movement disorders, cognitive impairment and depression. Along with trad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 97 publications
(144 reference statements)
0
31
0
1
Order By: Relevance
“…CKD patients have been reported to present with xerostomia (dry mouth), candidiasis, alteration in taste, periodontitis, dental caries and tooth loss [6,36]. Taste alteration is commonly reported among CKD patients although the underlying mechanism is not well understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CKD patients have been reported to present with xerostomia (dry mouth), candidiasis, alteration in taste, periodontitis, dental caries and tooth loss [6,36]. Taste alteration is commonly reported among CKD patients although the underlying mechanism is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of dry mouth may be as a result of fluid restriction, electrolyte imbalance and use of drugs that have xerostomia as side effects. Halitosis has been attributed to poor oral hygiene and uremic smell [36].…”
Section: Discussionmentioning
confidence: 99%
“…More than 100 uremic toxins have been identified thus far [ 39 ], and the pathological roles of protein-bound uremic toxins, such as indoxyl sulfate, have been actively studied. Accumulated uremic toxins are involved in CKD progression and complications, including cardiac dysfunction, sarcopenia, and cognitive function [ 19 , 40 , 41 ]. Notably, the relationship between the hemostasis system and uremic toxins in CKD pathogenesis has recently received considerable attention [ 17 , 18 , 19 , 20 ] ( Figure 1 ).…”
Section: Relationship Between Uremic Toxins and Tfmentioning
confidence: 99%
“…Recently, kidney disease has been proposed as a new modifiable risk factor for dementia [2]. It is reported that uremic toxins may have direct neurotoxic (astrocyte activation and neuronal death) and/or indirect action through vascular effects (cerebral endothelial dysfunction, calcification, and inflammation) [3,4]. Due to the endothelial dysfunction, small-vessel pathology has been used to clarify the link between kidney and cerebral microvasculature that share similar anatomical and physiologic features.…”
Section: Kidney and Nervous System In Ckdmentioning
confidence: 99%
“…In patients with CKD stages III to V, the relation between kidney and cognitive function was evaluated independently of the vascular risk factors. Among the other factors, the retention of uremic toxins, especially phosphate, has been again presented as a CKDspecific factor, accountable for structural and functional cerebral changes in patients with CKD [3,29]. Finally, the high phosphate level was associated with inflammation, stress, depression, and dementia, including Alzheimer's disease [30].…”
Section: Epidemiology and Etiopathogenesis Of Cognitive Impairment In...mentioning
confidence: 99%